Zebrina pendula Wandering Jew - Edward Gilman (EDIS, 2007)
This document is about the Zebrina pendula (wandering Jew or inchplant). It describes the plant’s vibrant purple-green leaves with silvery stripes and small, rose-pink flowers. The plant grows quickly, forming a dense mat, and prefers partial to deep shade with regular watering. It has moderate drought tolerance but poor salt tolerance. The document also notes that the plant is invasive and not recommended by UF/IFAS faculty. First time published Oct. 1999.